Author Correction: Epstein–Barr virus-encoded microRNA BART1 induces tumour metastasis by regulating PTEN-dependent pathways in nasopharyngeal carcinoma - Longmei Cai (Nature Portfolio, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.